PENINGKATAN KETERAMPILAN MENULIS RINGKASAN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS VIII 7 SMP NEGERI 1 BATUSANGKAR - Ilhami Desrina; Agustina .; Harris Effendi Thahar (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: This researce was aim to enhance students' writing skills summary. The writing ability of student still remain concerned under the circumstance, this fact due to student not trained well, low self esteem, low actualization to reveal their though and also the method of teaching is not appropriate with the purpose of study, that make student lack of motivation for writing. This researce was use description approach method with describe the process of improving writing skills through a summary of jigsaw cooperative learning model. The subjects were students of grade VIII 7 SMP 1 Batusangkar school year 2012/2013, amounting to 32 people. Data were obtained in the form of qualitative data collected through observation and field notes. Further quantitative data obtained through performance tests and questionnaire responses of students towards learning. From the data obtained a conclusion found that cooperative learning model jigsaw enhance the writing skills of student better. Moreover, cooperative learning model jigsaw application create the situation more interesting to student, make a student more comfortable, have some fun, due to this role model required student contribution and demand student more creative and dependable. Kata kunci: keterampilan menulis ringkasan, model pembelajaran kooperatif, tipe jigsaw